Revisiting the Miraculous Nature of the Qur’an in Sūrat al-Mu‘awwidzatayn: A Study from the Perspective of Tafsīr al-Iklīl fī Ma‘ānī al-Tanzīl by K.H. Misbah Musthafa - Faisal Diaulhaq (Journal of Islamic Thought and Contemporary Studies, 2026)
Along with the rapid advancement of technology and the progress of modern civilization, many messages conveyed in the Qur’an have increasingly demonstrated their truth and relevance. This phenomenon is closely related to the belief that the Qur’an constitutes a divine miracle bestowed upon the Prophet Muhammad. This study examines the concept of the miraculous nature of the Qur’an (i‘jaz al-Qur’an) as reflected in the interpretation of the Mu‘awwidzatayn by K.H. Misbah Musthafa. To address this issue, the study employs a library research method, utilizing as its primary source the exegetical work of K.H. Misbah Musthafa, Tafsir Al-Iklil fi Ma‘ani al-Tanzil. In addition, the research applies a socio-historical approach, namely an effort to understand Qur’anic texts by considering the historical and empirical circumstances surrounding the revelation of particular verses. The findings of this study reveal that K.H. Misbah Musthafa’s interpretive style in explaining the Mu‘awwidzatayn places significant emphasis on the aspect of asbab al-nuzul (occasions of revelation) of the two surahs. According to his interpretation, the Mu‘awwidzatayn functioned as shifa’ (healing or remedy) for the Prophet Muhammad against the effects of sorcery. This understanding is categorized within al-i‘jaz al-ghaibi, namely the miraculous dimension of the Qur’an associated with unseen realities. This study contributes to the broader discourse on Qur’anic miraculousness and the interpretation of the Mu‘awwidzatayn by presenting the perspective of a prominent Nusantara scholar within the tradition of Qur’anic exegesis.